Kotaraja dalam Arus Modernisme di Lombok Timur, 1990-2021 - Lalu Wahyu Andi Purnama; Muhammad Shulhan Hadi; Lalu Murdi; Badarudin Badarudin; Bambang Eka Saputra (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2023)
This study aims to; (1) analyze the history of the formation of Kotaraja Village; (2) describe the response of the people of Kotaraja Village to cultural elements that come from outside; (3) knowing the history of cultural development in Kotaraja Village before 1990; and (4) analyzing the cultural history of Kotaraja Village from 1990-2021. The approach used is qualitative by specifically using the historical method. In the historical method, there are stages that must be passed, namely, heuristics, source criticism, interpretation, and historiography. The result of this research is that Kotaraja Village has a relatively long history. This is closely related to the conception of culture in it. Since before 1990, Kotaraja Village has had a thick art and tradition. The cultural history of Kotaraja Village from 1990-2021 starts from the existence of the division of the Kotaraja Village area which is quite complex. The rapid developments in the field of culture after that were as follows: (1) the existence of Peresean Arts which was routinely carried out; (2) the establishment of the Jamiq Raudhatul Muttaqin Mosque as a Cultural Conservation Object; and (3) the release of the Kotaraja Village Tourism Information Center in 2021.